Ancient 'Black' Decorative Stones and the Ephesian Origin of Sculptural bigio antico. (5th January 2017) - Attanasio, D.; Bruno, M.; Prochaska, W.; Yavuz, A. B.
Abstract : Isotopic, EPR and petrographic studies aimed at establishing the provenance of sculptural bigio antico are reported, including 18 possible quarry sites and 21 ancient sculptures. The results demonstrate that the Belevi quarry, north‐east of Ephesos, above the more famous white marble quarry, was the major source of this marble. Nineteen artefacts belong to Belevi, whereas the precise origin of the remaining two is unknown, but must probably be found within the same area. The peculiar distribution of δ 13 C values both for Belevi and artefacts was crucial for inferring the correct provenance, subsequently confirmed by additional analytical and petrographic data.